Factors discouraging students from schooling: A case study at Junior Secondary School in Laos - Keoviphone, Chanthaboun; Wibowo, Udik Budi (REID (Research and Evaluation in Education), 2015)
This study is aimed at exploring and describing the factors discouraging Laos students from schooling at a secondary school in various contexts such as  classroom and school, individual student, family, and community contexts. Descriptive qualitative approach was used, and the framework of the study was formulated around the aspects of school and classroom situation, principal's management process, teachers' teaching organization and performance, parents' involvement and perception, and community's involvement and perception. The data were collected through observation, document analysis, and interview from 10 students, six teachers, one principal, one vice principal at Phonsyneua Junior Secondary School, and seven parents whose children were studying at this school. The finding shows that among the factors involved in students' schooling at secondary school, several factors discourage them. The teachers' performances were not perfect yet and some students' competency was not qualified enough. The students' parents were not highly committed and involved in their children's schooling. The community had little trust in schooling since they perceived that schooling costs a lot of money. To improve these discouraging factors, several actions should be taken into consideration. The principal should ask all the teachers to communicate the vision and missions to the students, or the vision and mission should be published and socialized in the school. The observations on teachers' instruction should be done by both the principal and senior teachers.